New design model of reinforced concrete beams in bending considering the ductility factor - Nogueira, C. G. [UNESP]; Rodrigues, I. D. (IBRACON - Instituto Brasileiro do Concreto, 2020)
Ductility is a recommended characteristic by different RC structures design codes around the world, such as ABNT NBR 6118 [2], ACI 318 [1] and EUROCODE 2 [4]. Despite the recommendation of ductility, the codes only define this criterion in a qualitative way, without quantification about how ductile the structure is, and not being able to stablish a ductility level in the design phase. In this context, this paper proposes a new design model of reinforced concrete beams in bending considering the explicit definition of the input parameter named ductility factor, which quantifies the structure’s ability to withstand displacement before it breaks.
Keywords: RC beams; concrete; ductility; damage